Influence of tilted surface alignment on flexoelectric domains in twisted nematic layers - Buczkowska, Mariola; Derfel, Grzegorz (Wydawnictwo Politechniki Łódzkiej, 2017)
The small deformations induced by electric field in twisted flexoelectric nematic layers were simulated numerically. The onedimensional (i.e. homogeneous over the whole area of the layer) and two-dimensional (i.e. spatially periodic flexoelectric domains) deformations were considered. It was shown that the periodic deformations do not arise if sufficiently high pretilt angle is imposed by the boundary conditions. The value of pretilt angle necessary for elimination of domains increases with the flexoelectric coefficient e33. This result is of practical meaning because the flexoelectric domains are undesirable from an applicative point of view since they destroy the homogeneous appearance of the area of an excited pixel of a display.

Niewielkie odkształcenia wywołane polem elektrycznym w warstwach skręconego nematyka były symulowane numerycznie. Badano odkształcenia jednowymiarowe (tj. jednorodne na całej powierzchni warstwy) i dwuwymiarowe (tj. przestrzennie okresowe). Wykazano, że odkształcenia okresowe nie powstają, gdy warunki brzegowe narzucają odpowiednio duży kąt nachylenia uporządkowania powierzchniowego. Jego wartość rośnie ze wzrostem współczynnika fleksoelektrycznego e33. Wynik ten ma znaczenie praktyczne, ponieważ występowanie domen fleksoelektrycznych w urządzeniach ciekłokrystalicznych jest niepożądane.
Wpływ ukośnego uporządkowania powierzchiowego na domeny fleksoelektryczne w skręconych warstwach nematyka
Keywords: nematics; flexoelectricity; director deformations; periodic patterns; uporządkowanie powierzchniowe; współczynnik fleksoelektryczny; odkształcenia jednowymiarowe; odkształcenia dwuwymiarowe